Recycling in situ of legume-fixed and soil nitrogen in tropical lowland rice - George, Thomas; Buresh, Roland J.; Ladha, Jagdish K.; Punzalan, Gloria (Wiley, 1998)
In tropical rice lowlands, vegetation during the dry‐to‐wet season transition (DTW) facilitates in situ recycling of N from soil or legume biological nitrogen fixation (BNF) to wet‐season flooded rice. As little is known, we examined the fates of soil N and BNF N in DTW vegetation in a 2‐yr study on a Philippine Tropudalf using 15N‐labeled residues produced and soil‐incorporated in situ. During DTW, Sesbania rostrata (Bremek. and Oberm.), mungbean [Vigna radiata (L.) R. Wilczek var. radiata], weeds, and a weed‐free fallow were subplots in dry‐season main plots of weedy, weed‐free, and frequently tilled fallows. Rice yield and N uptake were not influenced by dry‐season fallows, which did influence soil N and BNF N in DTW vegetation and, therefore, the amount of soil N lost, removed in a product or recycled. Build‐up and decline of soil NH4−N occurred within 5 wk of residue incorporation, before significant N uptake by rice. Rice yield and N uptake responded to greater recycled DTW N; N uptake averaged 103 kg ha−1 with 208 kg S. rostrata N ha−1, 79 kg ha−1 with 62 kg mungbean N ha−1, 61 kg ha−1 with 41 kg weed N ha−1, and 44 kg ha−1 with no residue N. Nitrogen‐15 estimates of N recovery by rice (20% of S. rostrata N, 27% of mungbean N, 16% of weed N) were lower than the actual increase in rice N uptake due to residues. High proportions of residue N remained in soil, but N loss of 32% was estimated for S. rostrata N. As green manure (GM) N is ineffective beyond the first few weeks of incorporation, incorporating much legume N to flooded rice wastes valuable BNF N. Unmet rice N demand beyond early crop stage is better supplied with fertilizer N synchronized with rice N demand. A mixture of native weeds and GM legume is likely to prevent build‐up of soil NO∐3−N and allow BNF while limiting total N accumulation in the DTW vegetation for use as GM.